Inquiry Based Learning Management (A Site Study At School Of Life Lebah Putih Salatiga) - Al Hikami, Muhammad Waston (2012)
The objective of the study is to describe, to understand, and to define the basic management in Inquiry based learning which is done by School of life Lebah Putih Salatiga. Specifically, the objectives of this study are as follows: 1) to describe the characteristic of inquiry based learning management which is applied by School of Life Lebah Putih Salatiga, 2) to describe the steps of inquiry based learning which is done by School of Life Lebah Putih Salatiga, 3) to find supporting factors and obstacles of inquiry based learning management which are conducted by School of Life Lebah Putih Salatiga. The type of this study is descriptive qualitative, as this study intends to investigate to illustrate or describe the state of the object/subject of study at the present time based on the facts that appear. Source of data is inquiry-based learning management process that took place in the school of life Lebah Putih Salatiga. The design used in this study is a site study, using ethnographic research. Source of the data are the Principal, teachers, parents and other relevant document. The writer used observations, in-depth interview and documentation to collect the data. The data finding showed that inquiry based learning applied in School of Life Lebah Putih Salatiga has characteristics as follows: the function of teacher is as facilitator in teaching learning process. The interesting learning applied in School of Life Lebah Putih focused on student's curiosity that is reflected by many appeared questions. The steps on inquiry based learning have three kinds of steps, namely: planning, application and evaluation. The obstacles on this model are on the lack of human resources who understand inquiry based learning model, the amount of supporting tools and equipments still need improvement, the passive students sometimes made the teaching-learning process ineffective, and the continuity of the inquiry based learning method at the higher grade.